2012
DOI: 10.1111/epp.2574
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of tomato borer, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) populations from Turkey to 7 different insecticides in laboratory bioassay

Abstract: The tomato borer, Tuta absoluta (Meyrick), was first recorded in Turkey in August 2009 and rapidly became a serious pest in the Mediterranean and Aegean coastal regions in field and greenhouse grown tomatoes. Currently, insecticides are considered one of the major tools for the management of T. absoluta in Turkey. This study, investigated the efficacy of 7 different insecticides, against T. absoluta in laboratory bioassays. To determine the lethal concentration (LC) values and feeding activity of the larvae, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
4
0
3
Order By: Relevance
“…According to the results of the field study, the researches denoted that spinosad was effective in controlling T. absoluta. Dağlı et al (2012) determined in a study investigated the efficiency of different insecticides on T. absoluta that spinosad and chlorantraniliprole+abamectin showed a hundred percent effect on the pest, but effects of metaflumizone and azadirachtin on the pest were lower. A study on management of T. absoluta with insecticides on tomatoes in both laboratory and greenhouse performed by showed that spinosad was effective in the ratio of 91% on T. absoluta.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the field study, the researches denoted that spinosad was effective in controlling T. absoluta. Dağlı et al (2012) determined in a study investigated the efficiency of different insecticides on T. absoluta that spinosad and chlorantraniliprole+abamectin showed a hundred percent effect on the pest, but effects of metaflumizone and azadirachtin on the pest were lower. A study on management of T. absoluta with insecticides on tomatoes in both laboratory and greenhouse performed by showed that spinosad was effective in the ratio of 91% on T. absoluta.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of the pest, many studies (Stol et al, 2009) have been conducted to relate its biology (Pereyra and Sanchez, 2006;Doğanlar and Yiğit, 2011;Torres et al, 2011;Öztemiz, 2012), ecology, management (Giustolin et al, 2001;Silva et al, 2011;Dağlı et al, 2012), effects of X-rays (Cagnotti et al, 2012), and reproduction as parthenogenesis (Megido et al, 2012). In some of these studies it is important to have knowledge of T. absoluta pupal characters.…”
mentioning
confidence: 99%
“…Conociendo que abamectina es menos eficaz que emamectina, factores de resistencia de 5,7 (Dağli et al, 2012), 8,9 (Silva et al, 2011) y 9,4 (Siqueira et al, 2001 en tuta a abamectina, se pueden considerar bajos, aunque siguen siendo más elevados que los que muestra cualquier población de tuta a emamectina (Tabla 4.1 y 4.2). Estos bajos niveles de resistencia a abamectina, pueden deberse a la baja dosis usada y a su rápida degradación (Clark et al, 1995).…”
Section: Poblaciónunclassified
“…Aún así, cabe destacar el rango de la CL 50 de dichas poblaciones de Grecia, el cual oscila de 31,8 a 159,5 ppm (Roditakis et al, 2013), valores considerablemente superiores a los observados en las tablas 4.3 y 4.4 (0,013-0,337 ppm). También son menos susceptibles a metaflumizona las poblaciones de Turquía ensayadas por Dağli et al, (2012), con un rango de la CL 50 de 153,2-1350 ppm y las estudiadas por Karaağaç (2015), con valores de 13,25 a 52,71 ppm, en poblaciones también turcas de tuta. A pesar de esos elevados valores de concentración letal, se vuelven a observar valores moderados de resistencia, 9 (Dağli et al, 2012) encuentran dentro del rango de valores de la CL 50 en poblaciones turcas de tuta, 10,9-88,1 ppm (Dağli et al, 2012).…”
Section: 32-susceptibilidad a Metaflumizonaunclassified
See 1 more Smart Citation